The Political Environment of Global Oral Health: Now is the Moment to Improve Equity - Jane Barrow; Ashiana Jivraj; Gene Bukhman; Mickey Chopra; Marko Vujicic; Habib Benzian (Annals of Global Health, 2023)
Harvard School of Dental Medicine’ Initiative to Integrate Oral Health and Medicine, in collaboration with Harvard’s Center for Integration Science and Global Health Institute, convened global experts in integration science and medical dental integration specifically, to call attention to the need for universal health coverage concepts that incorporate essential oral health services and thereby address equity and population health gaps. Across the globe, there are many innovative financial, clinical and educational programs that strive to provide comprehensive and universal healthcare that includes oral health. The goal of the symposium was to showcase successful examples of programs and policies that are improving health and quality of life, particularly for communities suffering disparities, through the integration of oral healthcare into primary and secondary levels of care. Symposium participants ranged from ministers of health to village healthcare workers to academics, who shared their successes and challenges integrating medical and oral healthcare. However, despite innovative examples spanning integration of care for infectious and noncommunicable diseases as well as social determinants, more work is required to: heighten awareness of the essentialism of oral health; strengthen the evidence for effective oral healthcare; and highlight the opportunity to improve health and equity through interprofessional collaboration. This commentary presents the key points from a subject matter expert discussion, theorizing through the lens of political economy about the challenges to advance the integration of oral healthcare within universal healthcare, and how the inspiring examples of success showcased throughout during the symposium surmounted systemic and cultural barriers to holistic care.